Whenua maa wai; he kootiti i eetahi koorero Land by water; a walk through some conversations - Cleave, Peter (Te Kaharoa, 2011)
This article reviews recent literature on water and land and ways of protecting them. The intention has been to browse around that literature, to walk through one or two conversations about water and guardianship without heading for a firm conclusion. This paper tries to stay close to the work discussed without necessarily advancing a distinct argument.